Helpful Tips for Chemigation of Papaya - Kati L. White; Teresa Olczyk; Jonathan Crane; Rafael Muñoz-Carpena; Tina Dispenza; Harry Trafford (EDIS)
Chemigation is a process by which an irrigation system is used for transport and delivery of an agrochemical, generally fertilizers or pesticides, to a crop. Often times, the irrigation system used in chemigation is drip irrigation. The purpose of this report is to provide some helpful tips for papaya growers interested in chemigation. This document is ABE 360, one of a series of the Department of Agricultural and Biological Engineering, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, Universtiy of Florida. First printing: August 2005.